Análise micro espacial sobre a incidência de fungo quitrídio em adultos de Crossodactylus schmidti, Gallardo, 1961 (Anura,Hylodidae) - Jeziorny, Jessica de Lara (2019)
Amphibian populations around the world detect serious risks, such as emerging diseases such as chytridiomycosis; they are of concern to today's amphibian biodiversity. To consider an occurrence of Batrachochytrium dendrobatidis (Bd) fungus in adults of Crossodactylus schmidti and an influence of seasonality on the infectious process are the objectives of the present work. Samples were taken from four streams in the Iguassu National Park (PNI). Each stream was sampled twice per season between January and October 2018. The incidence and prevalence of Bd infection can be modified by environmental factors and the statistics of the habitats in which the hosts are located. With the intention of verifying the relation of the environmental resources and selecting the habitat, with the incidence and intensity of the Bd, a set of measures were measured: the water and air temperature, the pH, the water coverage, the speed of the water, the width and depth of the streams as well as the cloacal rostrum length (CRC) of the C. schmidti adults. Were found adults in all streams sampled, with no record of dead deaths, totaling 119 animals. During the cold season, the fungus infected 50.94% of the samples collected and during the warm season, this percentage was 33.33%. The results found related to the average temperature, pH and sample selection coverage that the studied environment presents favorable conditions for the occurrence of Bd, however, none of the abiotic variables measured was statistically significant for the presence of the fungus. Was actually found in the four streams. Seasonality proved to be important for the incidence of infection, and was higher during the colder seasons (n = 119; Z = - 2.19; P = 0.028) and among the smaller population ((N = 119; Z = Although adults remain asymptomatic, the sublethal consequences of exposure to chytridiomycosis must be constantly monitored within the Iguaçu National Park in order to preserve the amphibian populations inserted there.